Application of probability theory in machine selection - Do Duc Trung; Manh Thi Diep; Duong Van Duc; Nguyen Chi Bao; Nguyen Hoai Son (Applied Engineering Letters)
Machine selection plays a crucial role as it impacts various aspects of production, including technical, economic, and environmental factors. Choosing a machine that ensures a balance among all these aspects is a complex task, as each type of machine involves numerous parameters that need consideration, and these parameters may sometimes conflict with one another. This study applies the probability method to select the optimal machine from the available options. It can be asserted that this is the first study utilizing probability for machine selection. The application of probability to choose the optimal machine has been carried out in five cases to select five different types of machines across various fields. The results of machine selection using the probability method have been compared with those obtained using other methods. This study has demonstrated that using probability ensures accuracy in machine selection.